HEDONISM REFLECTED IN THE BEAUTIFUL AND DAMNED NOVEL BY F. SCOTT FITZGERALD - APRILIYANI, DIAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : Hedonism, pleasure, lifestyle, standard, insider and outsiderHedonism is one of the lifestyle that is chosen by many modern people today. Hedonistic lifestyle aims to make people seek pleasure and happiness in ways that are sometimes beyond expected and the existing norms. The writer uses hedonism as the main theory to analyze because the problems of this novel are related to the luxurious lifestyle and temporary happiness. The writer also uses sociological approach because sociology is related to sociological aspect such as a group’s lifestyle and the division of social layers based on economy.This study shows that hedonistic lifestyle is reflected in the main characters of The Beautiful and Damned novel, Anthony Patch and Gloria Gilbert. They reflects hedonistic lifestyle and it becomes a habit. They will do anything to get what they want and they do not want to feel the hurt. They think the important things in their life are pleasure and happiness. Pleasure for Anthony is when he lives freely without hard work and gets his grandfather’s money. For Gloria, pleasure is a kind of worship from her husband to her beautiful face. Pleasure makes them selfish and do not care about other people.This behavior affects themselves and people around them. Hedonist leads to the formation of two social classes, in which people are grouped based on the standards they set. In sociology, it called insiders and outsiders. The main characters in this novel are included to insider because they share the same attachment and mission. Meanwhile the outsider is the group of people who are not included in insider group because these people do not meet the requirements in the standards of insider. They are neighbors who live in poverty.The impacts of hedonistic lifestyle occurred in the insider group, come in the form of breakdown of relationships between family members, friendships, self-esteem, and psychology. The first figure analyzed is Anthony Patch. When he got bankrupt, he  decided to hide the situation and pretends everything is fine. He does that because he does not want to lose his dignity and pride. Because of this problem, he suffered from depression symptoms and his mental being unstable.The effect of hedonistic lifestyle to the outsider appears when they become the subject of ridicule and humiliation by the insider.  The conclusion is hedonism is really reflected on main characters on The Beautiful and Damned novel and it brings some effects to themselves and to people around them. The suggestion for the future research, The Beautiful and Damned also could be analyzed with different theories like psychoanalysis and Marxism. The future researchers could dig deeper to find some interesting problems in this novel.